A Comparative Study of Kindergarten 3 Students’ Chinese Academic Achievement and Attitude Toward Learning Chinese Language According to Gender and Linguistic Family Background in a Private School in Bangkok, Thailand - xia, menglin; Rafael ©González González, Orlando (Scholar: Human Sciences, 2021)
The study was conducted to investigate the Kindergarten 3 (K3) students’ Chinese academic achievement and attitude toward learning Chinese language according to their gender and linguistic family background at a private school in Bangkok, Thailand. The study was carried out with a total of 124 K3 students at the target school during the second semester of the academic year 2019-2020. It was designed as a quantitative and comparative study. Two instruments were used in this study for data collection. One was the Attitudes Toward Learning Chinese as a Foreign Language Questionnaire, developed to measure students’ attitudes towards learning Chinese language. The other instrument was the Chinese Midterm Test, used to measure participants’ Chinese academic achievement. Descriptive statistics (means and standard deviations) and independent samples t-tests were performed on the collected data to address the research objectives driving this study. The findings indicated that girls had a significantly more positive attitude toward learning Chinese language than boys, and girls had also a significantly higher Chinese academic achievement than boys in the target school. Moreover, it was also found that students with bi- and multilingual family background had a significantly more positive attitude toward learning Chinese language than students with monolingual family background, and students with bi- and multilingual family background had a significantly higher Chinese academic achievement than those with monolingual family background. Based on the discussion of the findings, recommendations for action and further study are provided.